Urban development, small business communities and the entrepreneurialisation of English local government. Issue 2 (March 2018) - Raco, Mike; de Souza, Tatiana Moreira
Abstract : The paper draws on in-depth research on the impacts of urban regeneration programmes on small business communities in Haringey, London. It uses the Haringey case to document and describe the rolling out of more entrepreneurial forms of delivery-based urban policy and planning. It explores the relationships between austerity and local government finance; recent reforms to the planning system and the implementation of delivery-based, housing-focused urban regeneration programmes; and the types of urban built environment that are now emerging in cities. The discussion uses the example of small business communities to assess the impacts that contemporary planning interventions have on the form and character of urban economic development. It concludes by highlighting some of the broader implications for the planning of diverse cities and outlines future directions for research and analysis.